Fuel cell integrated unified power quality conditioner for voltage and current reparation in four‐wire distribution grid. Issue 1 (23rd January 2019) - Sundarabalan, Chinnayan Karuppaiyah; Puttagunta, Yeseswini; Vignesh, Vedhamoorthy
Abstract : Electrical and electronic devices, when exposed to one or more power quality problems, are prone to failure. This study aims to enhance the quality of power in three‐phase four‐wire distribution grid using fuel cell integrated unified power quality conditioner (FCI‐UPQC). The proposed FCI‐UPQC has a four‐leg converter on the shunt side and three‐leg converter on the series side. A combination of a synchronous reference frame and instantaneous reactive power theories is utilised to generate reference signals of the FCI‐UPQC. Also, this study proposes an adaptive neuro‐fuzzy inference system (ANFIS) controller to maintain the DC‐link voltage in the FCI‐UPQC. The ANFIS controller is designed like a Sugeno fuzzy architecture and trained offline using data from the proportional–integral controller. The obtained results proved that the proposed FCI‐UPQC compensated power quality problems such as voltage sag, swell, harmonics, neutral current, source current imbalance in the three‐phase four‐wire distribution grid. The presence of fuel cell in this work makes more effectiveness of the proposed system by providing real power support during supply interruption on the grid side.